PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID "FUNOLOGIE" UNTUK MATERI PETA DAN SISTEM FONEM BAHASA JERMAN PADA MATAKULIAH DEUTSCHE PHONOLOGIE - Flavia Konstantia Kartika Utami Dewi (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2018)
This research and development aims to develop an Android-based learning medium “Funologie” for the schema and the system of German phonemes materials. The development model used in this research is a model from Marrelli, Tondora, and Hoge. The procedure as mentioned above includes (1) Defining the Objectives, (2) Develop and Implement a Communication and Education Plan, (3) Plan the Methodology, (4) Identify the Model and Create the Model, (5) Apply the Model, and (6) Evaluate and Uptodate the Model. Based on the results of data analysis from validation and experiment process with descriptive quantitave method, the Android application “Funologie” is appropriate to be used as learning medium on Deutsche Phonologie course.